Peranan Koperasi Anugerah dalam Membangun Citra Merek Batik Pewarna Alami di Desa Ciwaringin Cirebon - Wina Elatifania; Dini Selasi (LPPM Universitas Koperasi Indonesia, 2026)
This study aims to analyse the role of Koperasi Anugerah Batik Ciwaringin in building the brand image of natural dye batik in Ciwaringin village, Cirebon. Koperasi Anugerah Batik Ciwaringin is the main organisation for developing batik printing with natural dyes in Ciwaringin, an area known for its unique motifs and traditional dyeing methods using natural materials such as leaves, fruit skins, and wood. The cooperative plays a strategic role in integrating economic empowerment functions with collective product branding efforts, including quality standardisation, human resource training, participation in exhibitions, and the use of digital media for promotion. Despite facing competition from cheaper batik printing, the cooperative is striving to build a strong brand image based on the environmental friendliness and cultural value of its products. This study uses a qualitative descriptive approach with a case study method. Primary data were obtained through in-depth interviews with the Chairman of Koperasi Anugerah Batik Ciwaringin, Mr Farhan Jazuli, as well as field observations and documentation. Data analysis was performed using the triangulation technique. The results of the study show that the Anugerah Cooperative plays a role in three main dimensions of brand image development: (1) strengthening the identity of the product based on natural dyes and zero waste, (2) promotion through national and international exhibitions and digital content, and (3) preserving the philosophy of the motif as a cultural narrative.